Implementasi Sistem Pemesanan Berbasis Digital Catalog untuk Meningkatkan Efisiensi Layanan di Cafe Wilayah Condet - Fiqri Andika Piliang; Johan Bastari; Filda Angellia (JURNAL TECNOSCIENZA, 2026)
The development of information technology has encouraged culinary businesses to adopt digital services in order to improve service quality. Cafe Sudut Timur Condet has implemented a digital catalog-based ordering system to create a more efficient and practical ordering process. This study aims to analyze the effectiveness of the digital catalog ordering system in improving service efficiency at Cafe Sudut Timur Condet. The research method used was a descriptive qualitative approach with data collection techniques through observation, interviews, and questionnaires distributed to managers and customers. The results showed that the implementation of the digital catalog was able to accelerate the ordering process, reduce service errors, and improve operational efficiency. However, the system still requires improvements in terms of interface design and ease of use for new customers. Therefore, the development of a more optimized digital catalog system is expected to enhance service quality and customer satisfaction in the digital era.